1998
DOI: 10.1002/(sici)1098-2396(199801)28:1<60::aid-syn7>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pharmacologic increases in brain GABA levels on cocaine-induced changes in extracellular dopamine

Abstract: Cocaine-induced increases in extracellular dopamine (DA) concentrations were measured using in vivo microdialysis techniques in the nucleus accumbens (NACC) of freely moving rats. In control animals, cocaine increased extracellular DA concentrations approximately 482% 60 min following administration, returning to baseline values 200 min later. When administered 2 h following an acute dose of gamma-vinyl-GABA (GVG, Vigabatrin), cocaine-induced increases in extracellular DA were reduced to approximately 365% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 56 publications
2
48
1
1
Order By: Relevance
“…γ-Vinyl GABA (GVG) is an anticonvulsant that elevates brain GABA levels by irreversibly inhibiting GABA transaminase, the enzyme responsible for GABA's metabolic degradation (Cubells et al, 1986). Systemic administration of GVG in rats has been reported to significantly inhibit cocaine self-administration (Kushner et al, 1999), cocaine-induced conditioned place preference , cocaine-induced enhancement of electrical brain stimulation reward (Kushner et al, 1997), and cocaine-induced increases in NAc DA Morgan and Dewey, 1998;Schiffer et al, 2000). However, the effect of GVG on cocaine-triggered reinstatement of drug-seeking behavior has remained unexplored.…”
Section: Introductioncontrasting
confidence: 82%
See 2 more Smart Citations
“…γ-Vinyl GABA (GVG) is an anticonvulsant that elevates brain GABA levels by irreversibly inhibiting GABA transaminase, the enzyme responsible for GABA's metabolic degradation (Cubells et al, 1986). Systemic administration of GVG in rats has been reported to significantly inhibit cocaine self-administration (Kushner et al, 1999), cocaine-induced conditioned place preference , cocaine-induced enhancement of electrical brain stimulation reward (Kushner et al, 1997), and cocaine-induced increases in NAc DA Morgan and Dewey, 1998;Schiffer et al, 2000). However, the effect of GVG on cocaine-triggered reinstatement of drug-seeking behavior has remained unexplored.…”
Section: Introductioncontrasting
confidence: 82%
“…However, the present data do not support that hypothesis: (1) a wide dose range of GVG, whether administered systemically (25-300 mg/kg, 1, 3 or 6 h prior to cocaine) or locally (1, 10, 100 and 1000 μM) into the NAc, altered neither basal levels of extracellular DA nor cocaine-induced increases in NAc extracellular DA in either cocainetreated rats (during reinstatement testing) or in drug naïve rats; and (2) the same doses of GVG dose-dependently increased, rather than decreased, NAc extracellular glutamate levels (Xi et al, unpublished data). Clearly, these findings conflict with previous reports that GVG inhibits cocaine-and other addictive drug-induced increases in NAc DA Morgan and Dewey, 1998;Schiffer et al, 2000). The precise reasons for this discrepancy are unclear.…”
Section: Non-da Mechanisms Underlying Gvg-induced Inhibition Of Drug-mentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, in an extensive series of preclinical rodent and primate studies using in vivo microdialysis and PET, respectively, we reported that GVG blocked drug and cue-induced increases in nucleus accumbens and striatal DA Gerasimov et al, 2001;Morgan et al, 1997;Morgan and Dewey, 1998). Further, we demonstrated that GVG blocked cocaine self-administration and cocaineinduced lowering of brain stimulation reward thresholds (Kushner et al, 1997).…”
mentioning
confidence: 61%
“…el tubérculo olfatorio v las áreas en el núcleo accumbens Produce un marcado limbicas como la corteza del incremento de la actividad locomotriz, el cual cíngulo, la frontal, la entorrinal y la perirrinal, puede ser bloqueado porfármacos neurolé~ticos, llamado sistema mesolimbico. por la inyección local de muscimol, un agonista gabaérgico, o por elevación de las concenSe le ha dado un Papel igualmente relevante en traciones de GABA a través de la inhibición de la este fenómeno a los sistemas serotoninérgicos enzima GABA transaminasa (20,21). y noradrenérgicos.…”
Section: Eferenciasunclassified